Pengaruh Non Performance Financing (NPF), Capitak Adequacy Rato (CAR), Pendapatan Operasional (BOPO), dan Return on Assets (ROA) terhadap (FDR) Studi Kuantitatif pada Bank Umum Syariah di Indonesia Periode 2019–2023 - Taupik Hidayat; Yossi Eriawati; Fajar Budiman (STAI YAPTIP, 2024)
ABSTRACT The Islamic banking industry in Indonesia has experienced rapid growth following the enactment of Law No. 21 of 2008, which provides a strong legal foundation for its operations. However, the sector still faces various challenges, including competition from conventional banks and economic instability. One important indicator for assessing the effectiveness of fund distribution is the Financing to Deposit Ratio (FDR), which reflects a bank’s ability to distribute financing based on the funds it has raised. This study aims to examine the impact of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), and Return on Assets (ROA) on FDR in Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the period 2019–2023. The research employs a quantitative approach using secondary data obtained from the annual financial statements of five Islamic banks that meet purposive sampling criteria. Data analysis techniques include panel data regression with Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) estimations. The findings show that NPF, CAR, and BOPO significantly affect FDR, while ROA has no significant impact. Simultaneously, these four variables collectively influence FDR. These findings offer valuable insights into the management of risk and operational efficiency in Islamic banks to improve financial stability and financing distribution capabilities. This study recommends that Islamic banks strengthen financing risk management and operational efficiency to enhance FDR and financial stability. Keywords: Non-Performing Financing, Capital Adequacy Ratio, Operating Expenses to Operating Income, Return on Assets, Financing to Deposit Ratio.